2022
DOI: 10.3390/molecules27165153
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Extraction of Proanthocyanidin Fractions from Ficus Species and Their Effects on Rumen Enzyme Activities In Vitro

Abstract: Three proanthocyanidin fractions per species were sequentially extracted by 50% (v/v) methanol–water, 70% (v/v) acetone–water, and distilled water from leaves of Ficus racemosa (fractions FR) and F. religiosa (fractions FRL) to yield fractions FR-50, FR-70, FR-DW, FRL-50, FRL-70, and FRL-DW. Fractions were examined for their molecular structure, effect on ruminal enzyme activities, and principal leaf protein (Rubisco) solubilization in vitro. All fractions except FRL-70 contained flavonoids including (+) catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
4
7
0
Order By: Relevance
“…This inhibition effect of phenolic compounds could be a result of their antimicrobial nature and the release of other metabolites during the fermentation process. Similar observations were recorded in cow rumen kinetics ( 14 ) from phenolic extracts of Ficus species ( 17 ) and methanolic tree leaves extracts of A. pendula ( 25 ). The released or break-down products of phenolic compounds from the plant extracts can be turned into new antioxidants ( 45 ) and that could reduce ruminal enzymatic activities.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…This inhibition effect of phenolic compounds could be a result of their antimicrobial nature and the release of other metabolites during the fermentation process. Similar observations were recorded in cow rumen kinetics ( 14 ) from phenolic extracts of Ficus species ( 17 ) and methanolic tree leaves extracts of A. pendula ( 25 ). The released or break-down products of phenolic compounds from the plant extracts can be turned into new antioxidants ( 45 ) and that could reduce ruminal enzymatic activities.…”
Section: Resultssupporting
confidence: 79%
“…The trend for reduction in the concentration of liberated rumen protein by the addition of compounds 1 and 2 with increasing concentrations and incubation times was also observed by others with condensed tannins extracted from Lotus pedunculatus ( 48 ), proanthocyanidins obtained from Ficus species ( 17 ), and tannin-rich forage leaves ( 49 , 50 ). This could be due to the steric interference at interaction sites of protease and receptors.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, a reduction of protein degradation in the rumen is associated with a lower production of ammonia and a greater flow of non-ammoniacal nitrogen to the duodenum and a higher amount of branched fatty acids. In this context, it has been observed that the proanthocyanidin fractions from the leaves of some species of Ficus or Anogeissus pendula and Eugenia jambolana , mainly composed of (epi)catechin, (epi)gallocatechin and their 4-phloroglucinol adducts, decrease the glutamic oxaloacetic ruminal and pyruvic transaminases as well as rumen R-Cellulase enzymes with consequent effects on the use of fibers and proteins [ 82 , 83 ]. Dietary condensed or hydrolysable tannins, supplied at adequate concentrations, are agreed to reduce in vitro concentrations of rumen NH 3 and branched-chain volatile fatty acids.…”
Section: Discussionmentioning
confidence: 99%